PERBEDAAN INTENSITAS DISMENORE PRIMER SEBELUM DAN SESUDAH PEMBERIAN INHALER STICK AROMATERAPI PEPPERMINT PADA REMAJA PUTRI - Ni Kadek Dwi Suryaningsih; Ni Wayan Armini; Ni Wayan Ariyani; Regina Tedjasulaksana; Gusti Ayu Marhaeni (Jurnal Gema Keperawatan, 2026)
Primary dysmenorrhea is a fairly common health problem during the menstrual cycle and often disrupts the activities of adolescent girls. Non-pharmacological management of menstrual pain is increasingly in demand, this is chosen because it is considered to have a higher level of safety and a low risk of side effects. One method used is peppermint aromatherapy through inhalation. The purpose of this study was to identify differences in the intensity of primary dysmenorrhea before and after administration of peppermint aromatherapy inhaler sticks to adolescent girls at STT Dharma Bhakti. This study used a pre-experimental research design with a one group pretest-posttest method. The sample was selected using a purposive sampling technique with 28 respondents. The instrument used in this study was the Numerical Rating Scale (NRS) to measure the level of pain before and after the intervention. Peppermint aromatherapy inhaler sticks with a dose of 0.5 ml were given and inhaled for 10 minutes, once a day on the first two days of menstruation. The results of the analysis showed a decrease in the median pain intensity from 5,00 to 2,00, and the average from 4,86 to 1,82. The Wilcoxon test produced a Z value = -4,737 with a p-value = 0,000 (p < 0,05), which indicated a significant difference between before and after administration of peppermint aromatherapy inhaler sticks. In conclusion, peppermint aromatherapy inhaler sticks are effective in reducing the intensity of primary dysmenorrhea, and can be used as a practical and non-invasive alternative therapy for menstrual pain in adolescent girls.